Down syndrome increases hospital length of stay in children with bronchiolitis. (March 2016) - Ting, Teck Wah; Chan, Hiok Yang; Wong, Petrina Poh Chen; Testoni, Daniela; Lee, Jan Hau
Background: Children with Down syndrome have an increased burden of respiratory infections. We hypothesized that children with Down syndrome hospitalized for bronchiolitis would stay longer compared with children without Down syndrome. Methods: We conducted a retrospective case–control study of children with Down syndrome who were hospitalized for bronchiolitis in Singapore from 2004 to 2012. Results: There were 27 and 43 admissions in the Down syndrome and control groups respectively. More children with Down syndrome had congenital heart defects (14 (52%) vs . none in controls). Children with Down syndrome stayed longer in hospital compared with controls (7 (interquartile range (IQR) 5–14) vs . 3 (IQR 2–4) days, p <0.001). In a subgroup analysis of patients without or surgically corrected congenital heart defects, children with Down syndrome still had a longer stay (6 (IQR 5–8) vs . 3 (IQR 2–4) days, p <0.001). Conclusion: Our study suggests that children with Down syndrome hospitalized for bronchiolitis stayed longer in hospital compared with those without Down syndrome.